IMPACT OF SCENARIO BASED EXERCISE ON ORGANISATION RESILIENCE IN CRITICAL INFRASTRUCTURE ORGANISATIONS - Ahmad, Arniyati; William Johnson, Christopher; Storer, Tim (Journal of Technology Management and Business, 2015)
Critical infrastructures are organisations that deliver vital services like telecommunication, energy and water suppliers to the community. Today, threats on critical infrastructure are differs from natural disasters, technical failures, man-made and cyber-attacks. Any disruptions on critical infrastructures could create a catastrophic damage. Protecting critical infrastructures and cultivating resilience has become a main agenda in many countries. Collaboration effort between public and private in crisis management through Scenario Based Exercise (SBE) was part of the agenda. SBE also known as Scenario Based Training (SBT) is a management tool used to train decision makers in crisis situations. However crisis management exercises through SBE appear to produce indistinct learning results which very limited in applicability. Using benchmark tool developed by Resilient Organisations Research at the University of Canterbury in New Zealand, this paper attempt investigate how SBE reflects the organisation resilience and determine the correlations between SBE and organisation resilience in critical infrastructures organisations.